2015
DOI: 10.1016/j.ejrad.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinoma and chronic mass-forming pancreatitis: Differentiation with dual-energy MDCT in spectral imaging mode

Abstract: Individual patient CNR-optimized energy level images and the NIC can be used to improve the sensitivity and the specificity for differentiating CMFP from PDAC by use of dual-energy MDCT in spectral imaging with fast tube voltage switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 34 publications
1
50
0
2
Order By: Relevance
“…The development of multidetector computerized tomography (CT) has improved the accuracy of CT in diagnosing CP and pancreatic neoplasms; however, the improved accuracy is only in cases where there is focal enlargement of the pancreas, which occurs in approximately 30% of CP cases, and these disorders have several overlapping morphologic features that limit its application [39]. Indeed, diagnosing CP by imaging techniques can miss cases in which morphological changes are not very prominent [37]; however, declining pancreatic exocrine secretion may precede detectable morphological changes [40].…”
Section: Diagnosis and Standard Of Care In Patients Presenting With Smentioning
confidence: 98%
See 1 more Smart Citation
“…The development of multidetector computerized tomography (CT) has improved the accuracy of CT in diagnosing CP and pancreatic neoplasms; however, the improved accuracy is only in cases where there is focal enlargement of the pancreas, which occurs in approximately 30% of CP cases, and these disorders have several overlapping morphologic features that limit its application [39]. Indeed, diagnosing CP by imaging techniques can miss cases in which morphological changes are not very prominent [37]; however, declining pancreatic exocrine secretion may precede detectable morphological changes [40].…”
Section: Diagnosis and Standard Of Care In Patients Presenting With Smentioning
confidence: 98%
“…Comparison of the FE-1 test with the direct pancreatic function tests, the secretin-CCK or secretin-cerulein tests[23,[39][40][41][42][43][44] Patients with clinical symptoms of malassimilation ULN for FE-1: 200 lg/g stool…”
mentioning
confidence: 99%
“…Because the energy spectrum curves of different substances show differences, differences of the energy spectrum curves in different tissue sources, characteristics and components can be estimated, which enables the differential diagnosis. It can be inferred that the energy spectrum curve can be used to differentiate the origin of tumors, benign and malignant tumors, and tumors with different differentiation degrees, moreover, the energy spectrum curve can be quantitatively analyzed to provide new diagnostic ideas [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…performed a single-center study on 35 patients and showed that DECT is able to differentiate MFCP from PDAC through normalized iodine concentrations both on arterial and pancreatic parenchymal phases. [ 9 ] In addition, significant differences were observed in the value of the slope K of the spectrum curve. Regarding the assessment of PDAC after chemoradiotherapy, a preliminary study was performed by Kawamoto et al .…”
Section: Current Technical Innovationsmentioning
confidence: 99%